The Generationing of Social Assistance Receipt and "Welfare Dependency" in Ontario, Canada. (11th September 2019) - Gazso, Amber; Baker Collins, Stephanie; Smith-Carrier, Tracy; Smith, Carrie
Abstract: Adopting a life course perspective, we explore, qualitatively, how receipt of social assistance in Ontario is generationally experienced. Data are drawn from a study of family and generational relationships with Ontario Works (OW), which included in-depth interviews with 31 participants who also had a child or parent on social assistance; we drew from three Canadian cities: Hamilton, London, and Toronto, Ontario. Our thematic analysis reveals that generation matters and in ways less confined than the ideation embedded in the discourse of welfare dependency. Through a life course lens, we find that while older and younger kin may concurrently access assistance, any generation's entrance onto it must be understood as varying by social, historical, and structural context, which itself varies over their individual life courses. We define this process as the "generationing" of social assistance receipt. We further reveal how this generationing interacts with gender, race, Indigeneity, and class. We therefore argue that the generationing of social assistance receipt prompts re-conceptualization of taken-for-granted ideation in the discourse of welfare dependency and, thus, is replete with policy implications.